Agro-Tourist Satisfaction in Sri Lanka: With Special Reference to Tourist Socio-Demographic and Destination Characteristics - Gunasekara, Indrachapa; Silva, Suranga (Journal of Sustainable Tourism and Entrepreneurship, 2022)
Purpose: The purpose of the study was to examine what factors are determining the level of satisfaction in agro-tourists and define the possible ways and means to enhance their satisfaction levels in promoting agro-tourism in Sri Lanka. There are four specific objectives in the study; to examine the current situation of the ago-tourism industry in Sri Lanka, to study the agro-tourism destination characteristics and socio-demographic characteristics of tourists, to analyze the relationship between the level of satisfaction, agro-tourism destination characteristics and socio-demographic characteristics of agro-tourist, and to discuss possible policy measures and management strategies to enhance tourist satisfaction and positive experience for agro-tourists in Sri Lanka. Research Methodology: This research utilized both qualitative and quantitative data collection methods. The gathered data were analyzed using five instruments; reliability test, inferential analysis, Pearson correlation analysis, regression analysis, and Kruskal Wallis test. Results: Ten possible policy measures and management strategies to enhance tourist satisfaction and positive experience for agro-tourists in Sri Lanka. Limitation: This research is limited to investigating the factors that affect the tourist satisfaction of agro-tourists. The scope focused on three areas, destination, tourist, and travel characteristics. The study focused on foreign tourists who have already visited Sri Lanka and been to agro-tourism sites. Contribution: This study is based on one such tourism concept which promotes in agricultural societies. The agro-tourism in Sri Lanka is identified as an important aspect of gaining the benefits of tourism. The satisfaction of the tourist must be ensured in the tourism industry for the long-term benefit of the business. The study contributes by suggesting actions and projects for agro-tourism satisfaction.